Optimizing Legal Protection: Addressing the Disparity of Sanctions Regarding Personal Names in Birth Certificates as Population Documents - Maskur, Ali; Shabir, Muslich; Hapsin, Abu; Rismana, Daud; Purwanto, Joko (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
This article discusses the issue of disparity in sanctions arising from the issuance of the Regulation of the Minister of Home Affairs of the Republic of Indonesia on Name Registration in Population Documents. A case in Tuban highlights a child who was unable to obtain a birth certificate because the name was too long to be entered into the Population and Civil Registration Office system. The regulation imposes restrictions on naming children, requiring a minimum of two words and no more than sixty characters. Non-compliance with this regulation can result in the non-issuance of a birth certificate, potentially rendering the child stateless. This situation contradicts UDHR Article 15, ICCPR Article 24, CRC Articles 7-8, and the 1945 Constitution Article 26 (1) on citizenship. The purpose of this study is to highlight the imbalance between regulatory rules and sanctions, demonstrating how lower-level regulations can violate higher-level rules. This research employs a qualitative, literature-based, and normative-doctrinal approach. Secondary data sources include Permendagri No. 73/2022, the Population Administration Law, the 1945 Constitution, and international regulations related to population and citizenship. The findings indicate that birth certificates reflect the state's responsibility to provide citizens with rights, including the right to identity. However, the sanction of not issuing a birth certificate due to regulatory non-compliance creates a disproportionate disparity in naming rights. Therefore, policy revision is necessary to optimize legal protection, making the system more equitable and in line with legal norms.